Lack of knowledge of physical activity guidelines: can physical activity promotion campaigns do better?. Issue 12 (5th December 2013) - Knox, Emily C L; Esliger, Dale W; Biddle, Stuart J H; Sherar, Lauren B
Abstract : Objectives: To identify the prevalence of knowledge of the current UK physical activity guidelines which were introduced in 2011 and prior physical activity guidelines (30 min on 5 days each week) within two large samples of UK adult's. To investigate whether knowledge of physical activity guidelines differs according to demographics such as ethnicity, age, education and employment status. Design: Descriptive cross-sectional study comparing two distinctive adult samples. Setting: National survey and online-administered survey conducted in England. Participants: The 2007 Health Survey for England provides data on knowledge of physical activity guidelines from 2860 UK adults (56% women, 89% white, 63% under 45 years old). In 2013, an online survey was disseminated and data were collected from 1797 UK adults on knowledge of the most recent physical activity guidelines. The 2013 sample was 70% women, 92% white and 57% under 45 years old. All adults in both samples were >18 years old and without illnesses/disorders likely to restrict physical activity. Main outcomes: Knowledge of physical activity guidelines in 2007 and 2013. Demographic correlates of knowledge of moderate-to-vigorous physical activity guidelines. Results: 18% of the 2013 sample accurately recalled the current physical activity guidelines compared with 11% of the 2007 sample who accurately recalled the previous guidelines. The differences in knowledge of physical activity guidelines existed for marital status, gender, age, education and employment status within both 2007 and 2013 samples (p<0.05). Men with lower education and employment status (unemployed including student and retired) and older adults were less likely to know physical activity guidelines (p<0.05). Knowledge of physical activity guidelines remained higher in the 2013 sample after controlling for demographic differences (p<0.05). Conclusions: Disadvantaged population groups are less knowledgeable about physical activity guidelines. Although knowledge of physical activity guidelines appears to have increased in recent years demographic disparities are still evident. Efforts are needed to promote health information among these groups.